ANALISIS TINGKAT KESEJAHTERAAN NELAYAN PEMILIK DAN NELAYAN BURUH PADA PERIKANAN GILL NET DI DESA KARANGSONG KABUPATEN INDRAMAYU - Rinanto, Dicky; Bambang, Azis Nur; M.Pi., Pramonowibowo (Journal of Fisheries Resources Utilization Management and Technology, 2013)
Territorial waters of Indramayu District is part of Indonesia territorial waters, which became the basis of fishing activities for fishermen. Indramayu district had HDI score of 69.45 in 2011. This reflects low quality of people at district of Indramayu. The purposes of this research was to analyze welfare level of Gill net owners and labours at Karangsong village Indramayu district with measuring the Human Development Index (HDI) and analyzed welfare levels in terms of the income Gill net owners and labours at Karangsong village Indramayu District. Research was conducted in April-May 2012. Research method used descriptive method, data collected includes welfare indicator which measures life expectancy (e0), measure the length of the average school population, mean years of schooling (MYS) and the literacy rate (Lit), and measure the economic capacity of Gill net fishermen reflected the value of purchasing power parity index (PPP). The results showed significant differences between the welfare level of Gill net owners and labour at Karangsong village Indramayu District. Life expectancy index Gill net owners and labours 62.15; education index owners and labour, respectively for 88.32 and 75.87; owners income index 98.27 and 61.69 for the labours, and IPM for the owner at 82.69 (high category), while HDI labours were 66.35 (middle high category).